Improving Learning Outcomes of High School Students through E-Magazine Learning Media Based on Qur'anic Values on Biodiversity Material - Hanim, Nafisah; Zahara, Nurlia; Dewi, Cut Ratna; Eriawati, Eriawati; Ahadi, Rizky; Irmaliana, Irmaliana (Universitas Islam Negeri Ar-Raniry, 2025)
Learning media based on qur'anic values significantly contribute to student outcomes. One reason for low learning outcomes in classes is that teaching materials rooted in Islamic values connect students with moral principles and shape their character, thereby strengthening the integration of science and religion. This research aims to improve student learning outcomes through e-magazine learning media based on qur'anic values. The research design is a quantitative experimental study with a pre-experimental method, specifically the One Group Pretest-Posttest Design. The sample consists of one class, X-3, totaling 30 students, selected using purposive sampling. The instrument used is a test consisting of 20 multiple-choice questions. Data were analyzed using the N-gain formula. The results showed an increase in student learning outcomes, with an average pretest score of 30.19. After instruction with e-magazine learning media based on qur'anic values, the posttest average improved to 80.19. The N-gain value was 0.72, indicating a high level of improvement. It can be concluded that the application of e-magazine learning media based on qur'anic values in biodiversity material significantly enhances student learning outcomes